How Islamic Religious Education Fosters Reflective Thinking Skills in a Multicultural and Democratic Context - Rafi, Mirzael; Qameer, Naufal; Salonen, Eric (Universitas Muhammadiyah Surakarta, 2025)
The low level of students’ reflective thinking skills in Islamic Religious Education (IRE) remains a significant challenge, largely due to the dominance of rote-based and textual approaches in instructional practices. This study aims to explore how IRE subject matter contributes to the enhancement of students’ reflective thinking, focusing on three key dimensions: problem understanding, evaluation and organization of knowledge, and solution development. Employing a qualitative descriptive approach, the study involved classroom observations and interviews with 58 high school students engaged in IRE learning. The findings reveal that IRE content—particularly materials with contextual and moral dimensions, such as social justice, tolerance, and prophetic narratives—effectively stimulates students' ability to identify real-life problems, evaluate information critically, and develop ethically grounded solutions based on Islamic values. These improvements are reflected in students’ increased engagement, thoughtful responses, and growing awareness of the relevance of Islamic teachings to contemporary issues. The study highlights that enhancing reflective thinking through IRE requires not only relevant content but also pedagogical approaches that are dialogical, participatory, and reflective in nature. Therefore, IRE can serve as a strategic educational vehicle in shaping students who are not only religiously committed but also critical, morally aware, and capable of responding to complex challenges in modern society.